A Scoping Review on Parametric model of Wind Generators - Geoconda Marisela Velasco Castelo,; Fabian Bastidas Alarcón,; Lidia Castro Cepeda,; Christian Giovanni Flores Arévalo, (Dominio de las Ciencias, 2024)
Parametric modeling for the installation of a second field of Wind Generators in the Villonaco Loja sector is based on the application of a set of general purpose and public license software, computational fluid dynamics (CFD). To generate mathematical models of the wind parameters of the Villonaco Loja sector, using the databases provided by CELEC. This work aims to carry out an art study on the information existing in the simulation of airflow, characterized by speed, pressure, tempera- ture, as well as work carried out in the identification of suitable areas for the installation of wind farms, energy production and the application of mathematical models in sectors located in different countries. The bi- bliographic review focused on open access databases using the PRISMA methodology, 50 articles were obtained meeting exclusion and inclusion criteria, however, a final stage was applied where the research questions were obtaining more detailed and representative answers, achieving arrive at a database of 40 articles, this being the most appropriate information for the development of the research.